Reading into Writing: Exploring Strategic Interplay in Academic Article Development - Juhana Juhana; Hanna Sundari; Widya Rizky Pratiwi; Nazirah Binti Md Yusof (Jurnal Pendidikan Progresif, 2026)
This study aims to determine the relationship between the reading and writing strategies employed by undergraduate students when composing academic work. A quantitative study was conducted in the English Education Department of a private university in Jakarta, Indonesia, involving 70 Academic Writing students. The data were gathered through questionnaires assessing specific reading and writing methods, including reading dimensions such as global understanding, information processing, and metacognitive awareness, and writing dimensions covering planning, execution, monitoring, and revision. The data were analyzed using descriptive and correlational statistics. This study was limited to students from one institution and relied on self-reported questionnaire data. Students consistently applied diverse reading and writing techniques across the writing phases, reporting moderate-to-high levels of strategy engagement. Strategies related to checking sources, avoiding plagiarism, and maintaining sentence and paragraph coherence were reported most frequently. In contrast, strategies such as visualizing texts and seeking peer feedback were used less often. The most notable finding was a strong, positive correlation between the two domains: reading strategies related to global understanding and metacognitive awareness showed the strongest association with writing strategies. This evidence suggests the importance of integrated literacy instruction in educational settings, given the clear interdependence of reading and writing skills. The study contributes empirical insights into how specific reading and writing strategies interact during academic article development, which may inform instructional practices in EFL academic writing contexts. Keywords: reading strategies, writing strategies, academic article development, integrated literacy instruction.